2015
DOI: 10.1097/ccm.0000000000000879
|View full text |Cite
|
Sign up to set email alerts
|

Septic Shock Sera Containing Circulating Histones Induce Dendritic Cell–Regulated Necrosis in Fatal Septic Shock Patients

Abstract: The study demonstrates a differential mechanism of dendritic cell death in patients with septic shock that is dependent on the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
(48 reference statements)
2
29
0
Order By: Relevance
“…More recently, circulating histones have been implicated as mediators of endothelial and organ dysfunction in sepsis (38), and several clinical studies have demonstrated their relevance to critical illness. Histones and their parent nucleosomes have been implicated in cardiac dysfunction (4,5), renal injury (12), and dendritic cell necrosis (24). In adults with trauma, nucleosome levels correlated with trauma severity scores, with histone levels correlating with Sequential Organ Failure Assessment scores and subsequent lung injury (2), consistent with our findings in this PARDS cohort.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…More recently, circulating histones have been implicated as mediators of endothelial and organ dysfunction in sepsis (38), and several clinical studies have demonstrated their relevance to critical illness. Histones and their parent nucleosomes have been implicated in cardiac dysfunction (4,5), renal injury (12), and dendritic cell necrosis (24). In adults with trauma, nucleosome levels correlated with trauma severity scores, with histone levels correlating with Sequential Organ Failure Assessment scores and subsequent lung injury (2), consistent with our findings in this PARDS cohort.…”
Section: Discussionsupporting
confidence: 80%
“…In five studies (3 adult sepsis, 1 adult aspiration ARDS, and 1 pediatric sepsis), nucleosome or histone levels have been demonstrated to be higher in nonsurvivors (4,12,24,40,41). In a cohort of septic adults (n ϭ 19), elevated histone H4 on day 1 predicted increased mortality at days 28 and 90 (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are now also waiting for the development of effective antihistone strategies to verify that this polycation is indeed the major "virulence factor" but maybe that histone does not function on its own, but in synergy with additional agonists. The following recent publications on histone and sepsis are worth reading [51][52][53][54][55][56][57][58][59][60][61].…”
Section: "Miracle Histones": Is It a Breakthrough In Sepsis Research?mentioning
confidence: 99%